Equality and Human Dignity in Islamic Education: Responding to the Stigma of Disability - Nazaruddin (Sekolah Tinggi Agama Islam YDI Lubuk Sikaping, 2026)
Stigma and discriminatory treatment of people with disabilities still frequently occur in educational settings, ranging from negative labeling, exclusion from learning activities, to low expectations of their abilities, thus hindering their access to and participation in the educational process. This phenomenon demonstrates the gap between the principle of human equality and the reality of discriminatory educational practices. This study aims to examine the concept of equality and human dignity from an Islamic educational perspective as a basis for responding to this stigma. The research used a qualitative approach with a library research method, examining primary and secondary sources related to the concept of humanity in Islamic education. The results of the study indicate that the concepts of karamah al-insan (human nobility), khalifah (human position as a trustee), and taqwa (parameters of nobility before God) can be synthesized into an ethical framework that affirms that physical or psychological differences do not make someone inferior, because human status is determined solely by piety, not physical condition or social background. This framework serves as a basis for Islamic education to eliminate stigma and build inclusive educational practices. This study concludes that Islamic education needs to reaffirm the principles of equality and human dignity as an ethical foundation for building an inclusive society for groups with disabilities.